Evangelicals and the early church : recovery, reform, renewal - Kalantzis, George; Tooley, Andrew (Eugene, OR : Cascade Books, 2012)
In this volume noted Evangelical historians and theologians examine the charge of the supposed "ahistorical nature of Evangelicalism" and provide a critical, historical examination of the relationship between the Protestant evangelical heritage and the early church. In doing so, the contributors show the long and deeply historical rootedness of the Protestant Reformation and its Evangelical descendants, as well as underscoring some inherent difficulties such as the Mercersburg and Oxford movements. In the second part of the volume, the discussion moves forward, as evangelicals rediscover the early church-its writings, liturgy, catechesis, and worship-following the "temporary amnesia" of the earlier part of the twentieth century. Most essays are accompanied by a substantial response prompting discussion or offering challenges and alternative readings of the issue at hand, thus allowing the reader to enter a conversation already in progress and engage the topic more fully. This bidirectional look-understanding the historical background on the one hand and looking forward to the future with concrete suggestions on the other-forms a more full-orbed argument for readers who want to understand the rich and deep relationship between Evangelicalism and the early church.
Prologue / Going deeper into the Bible : the church fathers as interpreters / Robert Louis Wilken -- Evangelical inattentiveness to ancient voices : an overview, explanation, and proposal / Christopher A. Hall -- John Wesley and the early church : history, antiquity, and the Spirit of God / Jeffrey W. Barbeau -- Why read Wesley : reading the fathers? : a response to Jeffrey W. Barbeau / D. Stephen Long -- The use and abuse of the Christian past : Mercersburg, the ancient church, and American evangelicalism / Darryl G. Hart -- Mercersburg doctrine as a double-edged sword : a response to Darryl G. Hart / Douglas A. Sweeney -- The Chicago call and responses / Elesha Coffman -- The Chicago call / David Neff -- Why study early Christian history and literature / Everett Ferguson -- Evangelicals and the public use of creeds / Scot McKnight -- A response to Scot McKnight / Daniel J. Treier -- Evangelicals and the rule of faith : Irenaeus on Rome and reading Christianity / D. Jeffrey Bingham -- A response to D. Jeffrey Bingham / Bryan Litfin -- Evangelicals, the Bible, and the early church / Michael W. Graves -- A response to Michael W. Graves / Timothy Larsen -- Evangelicals : are they the real Catholics and Orthodox? / Gerald L. Bray -- A response to Gerald L. Bray / Keith L. Johnson -- Epilogue: The radical*ness of the evangelical faith / George Kalantzis.
"The essays ... originated as a year-long discussion that celebrated the inauguration of the Wheaton Center for Early Christian Studies in the Fall of 2009, culminating in a conference held in the Spring of 2010 at Wheaton College that was an intentional collaboration between the Wheaton Center for Early Christian Studies and the Institute for the Study of American Evangelicals."--Introd., p. 1.
Includes bibliographical references (p. 253-262) and indexes.
Keywords: Evangelicalism -- Relations -- Primitive and early church, ca. 30-600.; Evangelicalism -- History; Church history -- Primitive and early church, ca. 30-600.; Church